Indirect Carbonation Of Coal Fly Ash For Carbon Dioxide Captured Via Mechanochemical Reaction - Omar Saifuddin, Nurul Athira (Universiti Sains Malaysia, 2018)
Many mineral wastes that produced in Malaysia have the potential candidates for CO2 mineral sequestration. One of them is by using coal fly ash. Therefore, to reduce CO2 from escaping towards the surroundings, carbonation (namely indirect carbonation) process is used to capture CO2. Indirect carbonation undergoes calcium extraction, followed by carbonation process using planetary ball mill. In extraction process, the influence of milling time, milling rotational speed and solid-liquid-ratio were explored. Increasing the milling time from 10 to 180 minutes and rotational speed from 100 to 400 rpm subtly increases the amount of calcium extracted. In carbonation process, KHCO3 was used as a carbonating agent in this study where the concentration was varied. At concentration from 2.5 to 5.5 mol/L, shows increasing of amount calcium being extracted. Addition to it, CO2 capacity of coal fly ash also increased due to the activation extraction of mineral particles especially calcium. The highest CO2 capacity and calcium extracted achieved were at 0.2310 g CO2/g CFA and 0.210 g Ca2+/g CFA. Using similar operating conditions, the carbonation was repeated using open vessel microwave. Planetary ball mill demonstrates higher carbonation efficiency compared to microwave. It gave positive impact shown by planetary ball mill where the amount of calcium extracted and the ability to sequestrate CO2 is higher as compared to microwave. Lastly, CFA were characterized using scanning electron microscopy (SEM) and FTIR spectrometer.